Root Canal Treatment of Mandibular Premolar Teeth with Different Root Canal Anatomies: Case Series - Eskibağlar, Mehmet; Kaya, Sadullah; Eskibağlar, Büşra Karaağaç (Selcuk University, 2021)
The correct diagnosis of root canal morphology and anatomy, and the cleaning, shaping and impermeable filling of the entire root canal system are the most important factors for successful root canal treatment. Mandibular premolar teeth generally have a single root and single canal anatomy. Other types of root canal anatomies apart from the single root and single canal are rarely seen in these teeth. In the radiological examination of these teeth, additional canals can be diagnosed using periapical films taken from different angles or dental volumetric computed tomography. In addition, careful examination of the pulp floor after the preparation of the endodontic access cavity and the use of magnifying tools facilitate the diagnosis of any canals that may be overlooked. In this case report series, endodontic treatment of mandibular premolar teeth with rarely seen different root canal anatomy is described. © 2021, Selcuk University. All rights reserved.
Farklı Kök Kanal Anatomisine Sahip Mandibular Premolar Dişlerin Kök Kanal Tedavileri: Olgu Serisi
Keywords: Anatomical variations; Endodontic treatment; Mandibular premolar